Engineering a genome‐reduced bacterium to eliminate Staphylococcus aureus biofilms in vivo - Victoria Garrido; Carlos Piñero‐Lambea; Irene Rodriguez‐Arce; Bernhard Paetzold; Tony Ferrar; Marc Weber; Eva Garcia‐Ramallo; Carolina Gallo; María Collantes; Iván Peñuelas; Luis Serrano; María‐Jesús Grilló; et al. (Molecular Systems Biology, 2021)
Abstract Bacteria present a promising delivery system for treating human diseases. Here, we engineered the genome‐reduced human lung pathogen Mycoplasma pneumoniae as a live biotherapeutic to treat biofilm‐associated bacterial infections. This strain has a unique genetic code, which hinders gene transfer to most other bacterial genera, and it lacks a cell wall, which allows it to express proteins that target peptidoglycans of pathogenic bacteria. We first determined that removal of the pathogenic factors fully attenuated the chassis strain in vivo. We then designed synthetic promoters and identified an endogenous peptide signal sequence that, when fused to heterologous proteins, promotes efficient secretion. Based on this, we equipped the chassis strain with a genetic platform designed to secrete antibiofilm and bactericidal enzymes, resulting in a strain capable of dissolving Staphylococcus aureus biofilms preformed on catheters in vitro, ex vivo, and in vivo. To our knowledge, this is the first engineered genome‐reduced bacterium that can fight against clinically relevant biofilm‐associated bacterial infections.